1974
DOI: 10.1159/000240698
|View full text |Cite
|
Sign up to set email alerts
|

Regional Blood Flow Changes in Neonatal Pigs in Response to Hypercapnia, Hemorrhage and Sciatic Nerve Stimulation

Abstract: Regional blood flow changes in response to hypercapnia, hemorrhage, and sciatic nerve stimulation were studied in 22 newborn piglets. Femoral, renal and/or carotid arterial flows were recorded simultaneously with aortic pressure and heart rate in piglets lightly anesthetized with halothane. Observations were made while ventilation was regulated to maintain arterial pH and pCO2 within the normal range, and when ventilation was adjusted to produce increased pCO2 and decreased pH uncomplicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
30
0

Year Published

1977
1977
1990
1990

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 8 publications
3
30
0
Order By: Relevance
“…However, in our studies in piglets, the fully integrated heart rate, arterial pressure, and regional flow response was not observed until the piglets were at least 2 weeks old (Buckley et al, 1976;Gootman et al, 1972;Reddy et al, 1974). Reflex bradycardia was rarely seen at the peak blood pressure rise during stimulation of sciatic nerve afferents or carotid sinus receptors (Buckley et al, 1976), although bradycardia did occur in response to direct stimulation of nucleus ambiguus (Gootman et al, 1972(Gootman et al, , 1978.…”
mentioning
confidence: 64%
“…However, in our studies in piglets, the fully integrated heart rate, arterial pressure, and regional flow response was not observed until the piglets were at least 2 weeks old (Buckley et al, 1976;Gootman et al, 1972;Reddy et al, 1974). Reflex bradycardia was rarely seen at the peak blood pressure rise during stimulation of sciatic nerve afferents or carotid sinus receptors (Buckley et al, 1976), although bradycardia did occur in response to direct stimulation of nucleus ambiguus (Gootman et al, 1972(Gootman et al, , 1978.…”
mentioning
confidence: 64%
“…It becomes~obvious ihat mean transit time expressed as ratio of pulmonary blood volume and flow must decrease considerably during development of piglets. Low volume-to-flow ratios can also be judged for the brain, kidney, and heart muscle by comparison of our results with relevant blood flow data in piglets (13,25,29,42).…”
Section: Age (Days)mentioning
confidence: 89%
“…Additionally, Guignard et al (9) has shown that p 0 2 was the same in newborns with moderate or severe impairment of renal function, suggesting factors other than arterial oxygen tension may be important. Using the piglet, Reddy et al (14) observed an increase in renal blood flow secondary to moderate degrees of hypercapnea and acidosis and a decrease in renal blood flow with severe hypercapnea and acidosis.…”
Section: Discussionmentioning
confidence: 99%